2016
DOI: 10.1016/j.jams.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Technical Challenges in Current Primo Vascular System Research and Potential Solutions

Abstract: Since Bonghan Kim's discovery of the Bonghan system (BHS) in the 1960s, numerous reports have suggested that the system is fundamental for maintaining mammalian life. The BHS is a circulatory system independent of the blood or the lymphatic system, forms an extensive network throughout the entire mammalian body, has been reported to be the acupuncture meridian, stores distinct types of stem cells, and appears to have some roles in cancer metastasis. Despite Kim's first report having been published as early as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…We clearly want to point out that the relationship between PVS and meridians still needs future exploration. This is in accordance with the article of Kang et al [43]. These authors also reported on identifying PVS with nanoparticles; however they also stated that the possible existence of PVS is still not known to many scientists [43].…”
Section: Seeking the Essence Of Meridianssupporting
confidence: 89%
“…We clearly want to point out that the relationship between PVS and meridians still needs future exploration. This is in accordance with the article of Kang et al [43]. These authors also reported on identifying PVS with nanoparticles; however they also stated that the possible existence of PVS is still not known to many scientists [43].…”
Section: Seeking the Essence Of Meridianssupporting
confidence: 89%
“…Up to now, the related real-time imaging articles on PV are still limited [ 27 ]. A section of vessel floating freely in the LV was frequently imaged in SFM and pCLE videos.…”
Section: Resultsmentioning
confidence: 99%
“…Kyung Aih Kang lished data), respectively. This subtype have been identified by many PVS scientists, although the ones inside the lymphatic vessels [15][16][17][18][19][20] are known to be easier to identify than the ones inside blood vessels [14,21,22] because lymphatic vessels and fluid are translucent, while blood contain large quantity of hemoglobin, a strong chromophore. Fig.…”
Section: Bonghan System Elucidated By Bong Han Kimmentioning
confidence: 99%